AKULTURASI PERKAWINAN SUKU SUNDA DAN SUKU JAWA DI DESA TANJUNG RATU KECAMATAN KATIBUNG KABUPATEN LAMPUNG SELATAN - Anis Marestiana; Ali Imron; Muhammad Basri (FKIP UNIVERSITAS LAMPUNG, 2013)
Abstract: Acculturation is the mixture of two or more cultures gradually for a long time butwithout losing the characteristics of culture itself. Based on the formulation of the problem inthis study, namely